Implementation Entropy And Electre II Method For Determining The Priority of Rebuilding a Damaged Bridge of Flood Disaster (Case Study In Trenggalek) - Junaidi, Arif; Irawan, Mohammad Isa; Mukhlash, Imam (Majalah Ilmiah Matematika dan Statistika, 2016)
ELECTRE II method is widely acknowledged to be used to analyze policies involving qualitative and quantitative criteria. Ranking procedure on the ELECTRE method was preceded by the forming of a directed graph as a representation of outranking relations. One of the weaknesses of ranking procedure based on the level / common procedure is if there were cycles in the graph that formed, the process becomes complicated. In this paper, ranking based on total domination by exploiting the transitive closures matrix formed that is from the representation of outranking relations in adjacency matrix, then compared with the ranking based on the level / general procedure. To determine the coefficient of weight for each criterion by using the entropy method. As an application, both ranking procedure used to determine the priority for rebuilding a damaged bridge of flood disaster in Trenggalek. Comparison of two procedures and the sensitivity analysis are done by changing some of threshold corcondance and discordance.